DOI: 10.26481/dis.20070628ms
|View full text |Cite
|
Sign up to set email alerts
|

Preferential processing in anxiety : selective attention & spatial affective simon effects

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 180 publications
(456 reference statements)
0
1
0
Order By: Relevance
“…It could be that increased cognitive load during a categorisation decision makes vigilance processes more vulnerable to distraction/attraction by threat, compared to the simpler decision about a target's location, or the even simpler decision that something happened. In an extensive review, Schooten (2007); chapter 1) listed an impressive number of studies using diverging designs, which nevertheless reported differential processing of threat cues/targets. Mogg and Bradley (1999) directly compared classification and position tasks and found that advantages for threat processing were equally strong in both designs.…”
Section: Discussionmentioning
confidence: 99%
“…It could be that increased cognitive load during a categorisation decision makes vigilance processes more vulnerable to distraction/attraction by threat, compared to the simpler decision about a target's location, or the even simpler decision that something happened. In an extensive review, Schooten (2007); chapter 1) listed an impressive number of studies using diverging designs, which nevertheless reported differential processing of threat cues/targets. Mogg and Bradley (1999) directly compared classification and position tasks and found that advantages for threat processing were equally strong in both designs.…”
Section: Discussionmentioning
confidence: 99%